Pengaruh Gaya Kepemimpinan: Kepuasan Kerja, Loyalitas Pegawai dan Komitmen di PT Lensa Potret Mandiri - Dian Sudiantini; Farhan Saputra (Formosa Journal of Sustainable Research, 2022)
Article The Effect of Job Satisfaction, Employee Loyalty and Employee Commitment to Leadership Style at PT Lens Portrait Mandiri. This research method uses quantitative methods, carried out using path analysis models and Structural Equation Model (SEM) analysis techniques based on Partial Least Square (PLS). The researcher used the SmartPLS 3.2.9 analysis tool to test the hypothesis. In conducting the research, the researcher used accidental sampling as many as 100 employee respondents who worked at PT Lens Portrait Mandiri. The research instrument in this study is the validity test and the reliability test for the Outer Model (Measurement Model) and Inner Model (Structural Model) tests that are sourced from SEM PLS. Data analysis techniques with descriptive analysis and path analysis. The results of this study are: 1) Job Satisfaction has no and no significant effect on Leadership Style; 2) Employee Loyalty has a positive and significant effect on Leadership Style; 3) Employee Commitment has no and no significant effect on Leadership Style